2006
DOI: 10.1177/089011710602100103
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity of Adults with Mental Retardation: Review and Research Needs

Abstract: Future research would be enhanced by including appropriately powered representative samples, by including comparison groups, by validating physical activity questionnaires, and by determining the accuracy of proxy respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
71
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 35 publications
4
71
0
5
Order By: Relevance
“…However, the research that has been conducted has found that many individuals with intellectual disabilities are highly inactive during their leisure time (Frey 2004), and not active enough to gain health benefits from the activities (Temple, Frey, and Stanish 2006). Children with intellectual disabilities seem to take less part in physical activities and rather more in recreational activities than children without disabilities (Umb-Carlsson 2008).…”
Section: Leisure and Barriers To Participationmentioning
confidence: 99%
“…However, the research that has been conducted has found that many individuals with intellectual disabilities are highly inactive during their leisure time (Frey 2004), and not active enough to gain health benefits from the activities (Temple, Frey, and Stanish 2006). Children with intellectual disabilities seem to take less part in physical activities and rather more in recreational activities than children without disabilities (Umb-Carlsson 2008).…”
Section: Leisure and Barriers To Participationmentioning
confidence: 99%
“…Since a part of the population of people with ID is historically inclined to obesity and in a poorer health condition -both as a consequence of insuffi cient physical activity and genetic diff erences (Frey & Chow, 2006;Yamaki, 2005; -it had been considered until recently that people with ID, on the periphery of society, should be resting and leading a "passive" life to prevent something worse happening to them (Goff man, 1991;Burnik & Brod, 2006). Consequently, motor defi ciency, which is refl ected in the information and energy components of movement (Filipčič, 2003;Frey & Chow, 2006;Temple et al, 2006), further increases with adolescence (Wall, 2004, in Zhang, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…People with MR are typically not included in large-scale population studies and there have been few attempts to document physical activity patterns or to identify factors that influence activity in these individuals [Temple et al, 2006]. Adults with MR have also received relatively less attention in health promotion efforts or physical activity campaigns.…”
mentioning
confidence: 99%
“…To date, there exists only one published study on whether children and youth with MR are meeting activity guidelines, therefore this age group was not included in the paper [Frey et al, unpublished data]. Readers are referred to Temple et al [2006] for a more inclusive review of the literature on physical activity and adults with MR.…”
mentioning
confidence: 99%